Hybrid renewable energy system design for a green port using HOMER Pro: A techno-economic assessment - Dinh, Gia Huy; Pham, Minh Tuan; Tran, Nguyen Bao Minh; Tran, Cong Minh; Nguyen, Tat Quyen; Le, Thanh Tien; Nguyen, Hoang Phuong (Center of Biomass & Renewable Energy (CBIORE), 2025)
Maritime plays an important role in the national economy since a large number of goods in the world are transported by sea, although maritime transport is found to generate the largest greenhouse gas emission among transportation means. For maritime activities, the port is considered the key chain in logistics, thus, the transformation of ports into sustainable energy centres has emerged as a major need in the worldwide initiative to decarbonize marine activities. This research provides a comprehensive techno-economic evaluation of a Hybrid Renewable Energy System (HRES) for Thi Nai Port, Vietnam, utilizing HOMER Pro software. The suggested system seeks to eradicate dependence on fossil fuels by including solar photovoltaics, wind turbines, a biogas generator, and sophisticated battery storage, therefore providing operational robustness. Simulation outcomes demonstrate that an ideal configuration, consisting of a 6,175-kW photovoltaic array, a 500-kW biogas generator, and a 2,357-kW converter, results in a net present cost of 44.6 million USD and a levelized cost of energy of 0.394 USD/kWh. Renewable sources constitute 100% of the installed and operational capacity, with yearly carbon dioxide emissions diminished to a modest 1,286 kg. The research verifies that hybrid renewable solutions may provide competitive economic returns, with a payback period of eight to ten years, while delivering substantial environmental advantages. The study portrays Thi Nai Port as a scalable paradigm for green port transformation, offering a repeatable framework for other mid-sized ports in Southeast Asia pursuing sustainable energy solutions.